2022
DOI: 10.1186/s12864-022-08623-4
|View full text |Cite
|
Sign up to set email alerts
|

Genome mining reveals polysaccharide-degrading potential and new antimicrobial gene clusters of novel intestinal bacterium Paenibacillus jilinensis sp. nov.

Abstract: Background Drug-resistant bacteria have posed a great threat to animal breeding and human health. It is obviously urgent to develop new antibiotics that can effectively combat drug-resistant bacteria. The commensal flora inhabited in the intestines become potential candidates owing to the production of a wide range of antimicrobial substances. In addition, host genomes do not encode most of the enzymes needed to degrade dietary structural polysaccharides. The decomposition of these polysacchari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 49 publications
1
1
0
Order By: Relevance
“…Based on the recommended 16S rRNA sequence 98.65% similarity thresholds for identifying novel bacterial species [11], these uncultured bacteria could be assigned four potential novel species, including Paenibacillus jilinensis sp. nov., validated in our previous studies [12], which fully demonstrate the diversity of chicken intestinal microbiota. In addition, these isolates were dominated by Lactobacillus (62.3% of strains).…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Based on the recommended 16S rRNA sequence 98.65% similarity thresholds for identifying novel bacterial species [11], these uncultured bacteria could be assigned four potential novel species, including Paenibacillus jilinensis sp. nov., validated in our previous studies [12], which fully demonstrate the diversity of chicken intestinal microbiota. In addition, these isolates were dominated by Lactobacillus (62.3% of strains).…”
Section: Discussionsupporting
confidence: 75%
“…In addition, a total of 89 strains were characterized as previous uncultured bacteria (Figure 1B), and based on the recommended 16S rRNA sequence 98.65% similarity thresholds for identifying bacterial species [11], it could be assigned potential for four novel species, among them, Paenibacillus jilinensis sp. nov. YPG26 has been validated in our previous studies [12], but we are also working to validate three additional novel species by whole genome sequencing-based phylogenomic analysis. To further investigate the effect of mediums on bacterial isolates, we analyzed and summarized the number of isolates from each medium; the results showed that the species of bacterial isolates increased significantly in the M2 and M3 medium supplemented with FBS or blood, respectively (Table 1).…”
Section: Microbial Diversity Of Chicken Intestinementioning
confidence: 99%